Triangular test applied to the clinical trial of azithromycin against relapses in Plasmodium vivax infections - Ranque, Stéphane (BioMed Central, 2002)
BACKGROUND: Sequential analysis enables repeated statistical analyses to be performed throughout a trial recruitment period, while maintaining a pre-specified power and type I error. Thus the trial can be stopped as soon as the information accumulated is considered sufficient to reach a conclusion. Sequential tests are easy to use and their statistical properties are especially suitable to trials with very straightforward objectives such as non-comparative phase II trials. We report on a phase II study based on the triangular test (TT) aiming at assessing the effectiveness of azithromycin in preventing Plasmodium vivax relapses. METHODS: To test whether the P. vivax relapse rate was either <12% or ≥ 45% in patients treated with azithromycin, a sequential analysis based on the TT was as used. Patients infected with P. vivax were treated with azithromycin, 1.2 g daily, for 7 days. The onset of a relapse infection was monitored. RESULTS: Five patients presenting with an acute P. vivax infection were included in the study. All the patients were initially cured. Three patients reported mild gastrointestinal adverse effects. When the third patient relapsed, the sample path crossed the upper boundary of the TT, and the trial was stopped. CONCLUSIONS: Using the triangular test, with only a small number of patients, we concluded that azithromycin was not effective enough in preventing P. vivax relapses to warrant further evaluation in phase III. It is suggested that a wider use of sequential analysis in phase II anti-infective drugs trials may have financial and ethical benefits.